Nature-based solutions for more sustainable cities : a framework approach for planning and evaluation - Croci, Edoardo; Lucchitta, Benedetta (Emerald Publishing Limited, 2021)
There is growing recognition and awareness that nature can help provide viable solutions to reduce vulnerability and generate value deploying the properties of ecosystems and the services they provide. Investing in nature can lead to substantial environmental, social and economic benefits by reducing pollution, decreasing energy costs, improving health and well-being and increasing resilience to climate change and natural disasters. Nature-Based Solutions for More Sustainable Cities makes a clear case of performances, impacts, and benefits generated by NBS in cities providing a comprehensive framework approach to understand the real and full potential of NBS at the urban level taking into account several aspects, from design and planning to socio-economic evaluation and financial issues. Given the multifunctionality of NBS, the book collects contributions from several international experts ensuring the interaction between different disciplines contributing to enrich and to disseminate knowledge about NBS.
Includes index.
Keywords: City planning -- Environmental aspects.; Sustainable development.; Environmental sociology.; Urban ecology (Sociology); Business & Economics -- Development -- Sustainable Development.; Urban & municipal planning.; elektronické knihy; electronic books